Spatial and temporal opportunities for forest resilience promoted by burn severity attenuation across a productivity gradient in north western Patagonia - Tiribelli, Florencia (2024)
BackgroundFire regimes in many biomass-rich ecosystems worldwide are dominated by high-severity fires. Many of these systems lack fire-resistant traits or post-fire regeneration strategies. Understanding under which environmental and weather conditions they experience less severe fire is crucial for maintaining their persistence in the landscape.AimsUnderstand the spatial and temporal conditions that allow burn severity attenuation across Patagonia?s productivity gradient.MethodsWe modelled burn severity as a function of topography, weather, vegetation and productivity.Key resultsLow severity was a rare phenomenon, affecting only 8% of the areas burned. The probability of burning with high severity followed a hump-shaped relationship with productivity. Low severity occurred in fires that burned under cool and wet summer conditions in areas with sparser fuels or in wetter and more productive environments but with discontinuous and wet fuels.ConclusionsAcross the regional gradient, ecosystems of intermediate productivity generally lack conditions for low burn severity. Temporally, low burn severity occurs in smaller fires burning in productive ecosystems during cool and wet summers.ImplicationsFuture climate scenarios of increasing aridity and temperature in the region will disfavour conditions for low burn severity, thus promoting fire-mediated transitions from forests to alternative states dominated by more fire-adapted flammable species (e.g. shrublands).